Does freer trade really lead to productivity growth? Evidence from Africa - Bresnahan, Lauren; Coxhead, Ian; Foltz, Jeremey; Mogues, Tewodaj (International Food Policy Research Institute, 2013)
We use firm-level data from the World Bank’s Regional Program on Enterprise Development, covering Ghana, Kenya, Nigeria, and Tanzania for 1991–2003. Econometric results confirm well-known relationships, such as a positive association between export intensity and TFP, which implies that more productive firms are more likely to select in to exporting.